Optimization of Surgical Treatment by Autoplasty in Patients with Primary Pterygium - Saidavzalzoda, Boboev Siyovush (American Journal of Bioscience and Clinical Integrity, 2025)
Pterygium is a pathological growth of the conjunctiva on the cornea, which can lead to decreased vision, discomfort and cosmetic defects. In the conditions of Uzbekistan, where solar activity, dry climate and dust factors have a significant impact on eye health, pterygium is a fairly common disease. Surgical treatment remains the main method of combating pterygium , but the relapse rate after standard surgical methods remains high. The autoplastic method, in which conjunctival autotransplantation is transplanted into the pterygium removal area , is a promising method that can significantly reduce the relapse rate. Optimization of this method, taking into account regional characteristics, requires more in-depth study in the context of Uzbekistan.